2018
DOI: 10.1038/s41598-018-21387-w
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cells are dynamic reservoirs of cytokines

Abstract: Red blood cells (RBCs) have been shown to affect immune function and can induce inflammatory responses after transfusion. The transfusion of washed RBCs can significantly reduce adverse effects, however, the soluble factors that may mediate these effects have not been identified. Previous studies have identified, but not quantified, a small number of chemokines associated with RBCs. We isolated RBCs from healthy volunteers and quantified of a panel of 48 cytokines, chemokines, and growth factors in the lysate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 41 publications
1
79
0
2
Order By: Relevance
“…In addition, INF-γ contributes to apoptosis of the erythroid progenitors and decrease the EPO receptor expression [17]. 3) RBC are dynamic reservoirs of cytokines [18]. Decreased deformability of RBC in severe illness leads to RBC lysis and release of intracellular contents into the circulation [19], including some inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, INF-γ contributes to apoptosis of the erythroid progenitors and decrease the EPO receptor expression [17]. 3) RBC are dynamic reservoirs of cytokines [18]. Decreased deformability of RBC in severe illness leads to RBC lysis and release of intracellular contents into the circulation [19], including some inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are all highly potent stimulators of the immune system and the endothelium and could be responsible for part of immune modulation effects seen in some patients post‐transfusion . In addition, a recent study showed that RBCs harbour a number of cytokines which are released upon haemolysis . This could explain the increase in cytokine concentration in RCC supernatants during HS resulting from increased RBC breakdown .…”
Section: Discussionmentioning
confidence: 99%
“…SCD is characterized by a pro-inflammatory state leading to high plasma cytokines levels. Karsten et al (101) recently showed that 46 cytokines can be detected in RBCs lysates of healthy individuals, and their median concentrations in RBCs were 12-fold higher than in plasma. Among them, the authors reported the presence of IFN-γ, IL-1β, IL-18, TNFα as well as several chemokines, such as IL-8 and RANTES.…”
Section: Inflammation and Rbcsmentioning
confidence: 99%